SELLIN: a case study on opportunity creation for sustainable growth - Adriana Bonomo-Odizzio; Patricia Correa-García; Catherine Krauss-Delorme (GECONTEC, 2024)
The purpose of this case study is to present Sellin as a socially innovative enterprise in Uruguay and to contribute to university education in the knowledge of a triple impact business model. Sellin is a platform that brings together micro and small producers from all over the country with the aim of disseminating and marketing their products nationally and internationally. Its purpose is focused on providing them with opportunities for sustainable growth, avoiding territorial uprooting and generating a triple impact. The methodology developed is the case study, with secondary research through field work with semi-directed interviews and analysis of secondary sources. The methodological development includes pedagogical notes and a work plan for the teacher. The case study allowed us to understand that Sellin is a successful social innovation venture that has managed to grow and scale in a sustainable way and that is considering the continuous professionalization of its business model, integrating the challenge of consolidating the sustainability chain by connecting key partners as partners for impact.